2019
DOI: 10.3389/fevo.2019.00371
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic Analysis and Identification of Factors Impacting the Diffusion of Foot-and-Mouth Disease Virus in Africa

Abstract: Foot and mouth disease (FMD) is endemic in sub-Saharan Africa. Due to the complexity of the disease epidemiology and the lack of data available, there is a need to use modeling approaches to fill the gaps in our understanding of the virus circulation on this continent. Using a phylogeographic approach, we reconstructed the circulation of FMD virus serotypes A, O, SAT1, and SAT2 in Africa and evaluated the influence of potential environmental and anthropological predictors of virus diffusion. Our results show t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 53 publications
10
31
0
3
Order By: Relevance
“…However, the most closely related clade in the ML tree included numerous sequences from Southern Africa (Figure ), similar to SAT1. The results of our analysis strongly suggest Kenya as the origin for the currently circulating SAT2 viruses as well as the epicentre for their dispersal to other Eastern African countries (Figures b and b), a pattern which has also been described for serotypes A and O (Duchatel et al, ). Interestingly, the mean count of relative forward and backward transitions between each pair of East African countries for SAT2 is noticeably higher than for SAT1 (Figure b).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the most closely related clade in the ML tree included numerous sequences from Southern Africa (Figure ), similar to SAT1. The results of our analysis strongly suggest Kenya as the origin for the currently circulating SAT2 viruses as well as the epicentre for their dispersal to other Eastern African countries (Figures b and b), a pattern which has also been described for serotypes A and O (Duchatel et al, ). Interestingly, the mean count of relative forward and backward transitions between each pair of East African countries for SAT2 is noticeably higher than for SAT1 (Figure b).…”
Section: Discussionsupporting
confidence: 81%
“…Growing evidence suggests that the divergence times of currently circulating SAT viruses were a result of geographical isolation and population bottlenecks in African FMDVs following the Great African Rinderpest Pandemic (i.e., between 1887 and 1897), which caused a mass die‐out of FMDV‐susceptible hosts. Furthermore, it is hypothesized that contemporary SAT viruses were re‐introduced from the remaining buffalo populations, which influenced the current genetic diversity and geographical distribution of SAT FMDVs (Duchatel, Bronsvoort, & Lycett, ; Lasecka‐Dykes et al, ; Omondi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas our results showed that serotypes O and A have spread worldwide, serotypes Asia1 and SATs remained non-pandemic and confined in their endemic regions [82,95]. Since there is a lack of detailed sequences data available, especially for African countries, it is important to note that these results may vary with a better representation of the currently circulating virus, although they support what has been previously described [59,78,79,82].…”
Section: Asia1 and Sat Serotypessupporting
confidence: 78%
“…Several studies have explored the spatiotemporal evolutionary dynamics of FMDV in different parts of the world, mainly focusing on the diffusion patterns across its endemic regions: Asia and Africa [31,48,[55][56][57][58][59] However, studies considering all serotypes are only available within small geographic regions, and global studies only assessed some of the viral serotypes [55,60].…”
Section: Introductionmentioning
confidence: 99%
“…FMD has low mortality but significant losses of production that may lead to important economic losses [61]. Although research has been conducted to understand the impact of FMD virus [62,63]. Previous studies show that the introduction of FMD virus in FMD free countries cause a severe impact on national economies [64].…”
Section: De-population Of Infected Animalsmentioning
confidence: 99%